Makan Bergizi Gratis di Era Prabowo-Gibran: Solusi untuk Rakyat atau Beban Baru? - Aji, Wahyu Trisno (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This article aims to explain the Free Nutritious Meals (MBG) or Free Lunch program which is the mainstay vision and mission of President and Vice President Prabowo-Gibran. This article uses a qualitative method with literature study data sources through a descriptive-analytical approach. The Free Meals program has a noble goal, one of which is to improve quality and healthy Human Resources (HR) to produce a great and golden generation in 2045. Although there is a question mark, how can this program run well if in one day the budget needs 800 billion, where does the budget come from to run the Free Nutritious Meals program every day. Of course the debate on this matter is still not over, especially since the Free Lunch issue is about nutritional standards, not about free expensive food.